GPR35/CXCR8 IS THE RECEPTOR OF THE MUCOSAL CHEMOKINE CXCL17 - Maravillas-Montero, José L. (J Immunol, 2014)
Chemokines are chemotactic cytokines that direct the traffic of leukocytes and other cells in the body. Chemokines bind to G protein-coupled receptors (GPCRs) expressed on target cells to initiate signaling cascades and induce chemotaxis. Although the cognate receptors of most chemokines have been identified, the receptor for the mucosal chemokine CXCL17 is still undefined. Here we show that GPR35 is the receptor of CXCL17. GPR35 is expressed in mucosal tissues, in CXCL17-responsive monocytes, and in the THP-1 monocytoid cell line. Transfection of GPR35 into Ba/F3 cells rendered them responsive to CXCL17 as measured by calcium mobilization assays. Furthermore, GPR35 expression is downregulated in the lungs of Cxcl17(-/-) mice, which exhibit defects in macrophage recruitment to the lungs. We conclude that GPR35 is a novel chemokine receptor, and suggest that it should be named chemokine (C-X-C motif) receptor 8 (CXCR8).